Complete mitochondrial genome sequence for the Thrips hawaiiensis (Thysanoptera: Thripidae) - Wang, Yunyu (Mitochondrial DNA B Resour, 2021)
Thrips hawaiiensis (Morgan) (Thysanoptera: Thripidae) is a common Thysanoptera insect widely distributed in Asia and the Pacific, it damages various plants. In this study the complete mitochondrial genome of T. hawaiiensis was sequenced and characterized by using next-generation sequencing technique. The total length of the complete genome is 15,357 bp and A + T content of 77.8% (GeneBank accession No. MW582621). The T. hawaiiensis mitochondrial genome consists of 13 protein-coding genes (PCGs), 2 ribosomal RNA genes, 22 transfer RNA genes (tRNAs) and 2 non-coding control regions (Dloop region). According to previous studies, only a few complete mitochondrial genomes from Order Thysanoptera have been reported. Thus, T. hawaiiensis complete mitochondrial genome sequence reported will provide molecular information for mitochondrial genome research on Thysanoptera.